Perceptions and experiences of young adults and their healthcare team of the D1 Now type 1 diabetes intervention. - Elizabeth M McCarthy; Sean F Dinneen; Molly Byrne; Eimear C Morrissey; Dympna Casey (PLoS ONE)
Background Young adults (18-25 years) with type 1 diabetes can have high blood glucose levels, increasing their risk of complications. The D1 Now intervention aimed to improve outcomes, using a young adult-centred approach, comprising three components: an interactive messaging system, agenda setting tool, and support worker. A pilot randomised controlled trial was conducted to assess acceptability and feasibility of this novel intervention. Aim To explore perceptions and experiences of young adults and healthcare staff participating in the intervention arms of the D1 Now pilot randomised controlled trial. Methods A descriptive qualitative approach using semi structured interviews was used to collect data between May 2020, and January 2021 from sixteen young adults and ten healthcare staff Interviews were conducted online using MS Teams. Thematic analysis was used to analyse the data. A patient and public involvement approach was used with the D1 Now Young Adult Panel deployed from the outset to design and contribute to the study. Both written consent in advance and verbal consent was given by all participants for the online interviews that were video and audio recorded according to individual participant preference. Results Themes were developed separately for young adult and healthcare staff participants. Two themes were developed from the young adult data, 1) 'empowerment' and 2) 'perceptions and experiences of the intervention'. One theme was developed from the healthcare staff data, 'perceptions and experiences of delivering the intervention'. All participants highlighted that the agenda setting tool and the support worker empowered the young adults as they could focus the consultation process on what mattered most to them. However, the interactive messaging system was perceived as unsuitable by many mainly because the technology was outdated. Overall, the perceived impact of participating in the study was positive. Conclusions Understanding participants perceptions and experiences of taking part in the D1 Now intervention is crucial. The lessons learnt can be used to further refine and develop the intervention with a view to measuring its effectiveness, in a future definitive trial.